Sistem Pendukung Keputusan Pemilihan Guru Les Terbaik Menggunakan Metode Fuzzy AHP - Rasyidah; Rizqul Fauzy; Yuhefizar (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2024)
This research aims to develop a decision support system that can help English School Indonesia in choosing the best tutor by using the Fuzzy-AHP (F-AHP) method. The Fuzzy-AHP method combines Analytical Hierarchy Process (AHP) with fuzzy logic, which can overcome uncertainty and imprecision in criteria assessment. The first step in this research is to conduct a literature study to understand decision support systems, AHP methods, fuzzy logic, and their implementation in tutor selection. Furthermore, data and information related to tutor selection criteria will be collected from English School Indonesia through interviews and surveys. Fuzzy-AHP method will then be applied to build a hierarchical structure of criteria in selecting the best tutor. The criteria can include performance, attendance and discipline, communication skills, target achievement, competence